2020
DOI: 10.1002/aic.17087
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of cellular internalization and expulsion of unstructured D‐chirality cell penetrating peptides

Abstract: Most cell penetrating peptides (CPPs) are unstructured and susceptible to proteolytic degradation. One alternative is to incorporate D‐chirality amino acids into unstructured CPPs to allow for enhanced uptake and intracellular stability. This work investigates CPP internalization using a series of time, concentration, temperature, and energy dependent studies, resulting in a three‐fold increase in uptake and 50‐fold increase in stability of D‐chirality peptides over L‐chirality counterparts. CPP internalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Isomer is another factor affecting the function of CPPs [ 10 , 64 , 65 , 66 , 67 , 68 ]; a different number of arginine optical isomers in the peptide sequence are proved to affect the uptake efficiency of the delivery peptides. Verdurmen et al [ 69 ] firstly reported the differences in the uptake of L-CPPs (R 9 ) and their D-counterparts (r 9 ); the results demonstrated that cationic L-CPPs (R 9 ) were taken up more efficiently than their D-counterparts (r 9 ) in MC57 fibrosarcoma and HeLa cells but not in Jurkat T leukemia cells (the sequences of the peptides were shown in Table 1 ).…”
Section: Peptide Design Of the Arginine-rich Cppsmentioning
confidence: 99%
“…Isomer is another factor affecting the function of CPPs [ 10 , 64 , 65 , 66 , 67 , 68 ]; a different number of arginine optical isomers in the peptide sequence are proved to affect the uptake efficiency of the delivery peptides. Verdurmen et al [ 69 ] firstly reported the differences in the uptake of L-CPPs (R 9 ) and their D-counterparts (r 9 ); the results demonstrated that cationic L-CPPs (R 9 ) were taken up more efficiently than their D-counterparts (r 9 ) in MC57 fibrosarcoma and HeLa cells but not in Jurkat T leukemia cells (the sequences of the peptides were shown in Table 1 ).…”
Section: Peptide Design Of the Arginine-rich Cppsmentioning
confidence: 99%
“…The integration of non-natural amino acids, a determined secondary structure, or an increased backbone inflexibility could achieve CPPs stability and protect them against degradation. 18 So, the development of other CPPs that do not present such issues is a goal for the scientific community to apply them in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It is known direct penetration and endocytosis are the main pathways for the cellular uptake of nanomaterials. [ 34 , 35 ] To clarify if the cellular uptake of WP5⊃D/DL/L‐Arg+DOX+ICG supramolecular nanoparticles is mediated by direct penetration pathway (energy independent), the cellular uptake experiments were performed at 4 °C, with the co‐incubation of WP5⊃D/DL/L‐Arg+DOX+ICG nanoparticles and Hela cells for 24 h. As shown in Figure S17 (Supporting Information), the internalization of WP5⊃D/DL/L‐Arg+DOX+ICG into CT26 cells was completely inhibited at this condition, suggesting the endocytosis‐based cellular uptake of WP5⊃D/DL/L‐Arg+DOX+ICG. To further demonstrate the specific endocytosis pathway, inhibitors, i.e., chlorpromazine (inhibitor of clathrin‐dependent endocytosis), nystatin (inhibitor of caveolin‐dependent endocytosis), and wortmannin (inhibitor of micropinocytosis‐mediated endocytosis) were employed for the pretreatment of CT26 cells.…”
Section: Resultsmentioning
confidence: 99%